PENGARUH PEMBERIAN DYNAMIC NEUROMUSCULAR STABILIZATION TERHADAP PENURUNAN NYERI PADA LOW BACK PAIN MYOGENIC et causa HIPERLORDOSIS LUMBAL di RSUD Dr. HARDJONO PONOROGO - Febriany, Restu Tama; Wijianto, Wijianto; Kingkinnarti, Kingkinnarti (Journal of Innovation Research and Knowledge, 2023)
Introduction: Low Back Pain is a health problem in almost all countries in the world. It is almost certain that 50-80 percent of people aged 20 years and over have experienced LBP. Generally suffered by women aged 60 years and over more often feel lower back pain. The prevalence of low back pain cases is estimated at one year to be 38.0% ± 19.4% and is higher in the elderly population. Hyperlordosis is one of the factors that causes mechanical low back pain. Based on the existing prevalence of women who tend to experience hyperlordosis, because women’s physiological muscle abilities are lower than men’s. Hiperlordosis causes the point of body weight will shift forward. Hyperlordosis, this is because the point of body weight will shift forward. As compensation, the back muscles will work harder. Purpose: this study was to determine the effect of dynamic neuromuscular stabilization on reducing pain in low back pain myogenic et causa lumbar hyperlordosis. Methods: patients are given dynamic neuromuscular stabilization for 4 weeks 5x meetings with doses 3 times a week each session is 30 minutes. Results: evaluation was carried out using Range Of Motion (ROM), Manual Muscle Testing, Numeric Rating Scale. Conclusion: There is an increase in Manual Muscle Testing and a decrease in pain on the Numeric Rating Scale, so that this intervention is very effective in reducing back pain caused by incorrect posture.